Pesticide Induced Physiological and Behavioural Changes in an Estuarine Teleost Therapon jarbua (Forsk) - Lingaraja, T. (Fishery Technology, 1978)
Static bioassays were conducted with pesticides like PP'-DDT, Dimethoate (Rogor)* and Carbaryl (Sevin) to determine the median lethal concentrations (LC60) on an estuarine teleost Therapon jarbua (Forsk). The respiration rates of fishes exposed to pesticides, as well as those of controls were determined. Respiration abnormalities were noticed in treated fishes. The metabolic rates are generally higher in treated fishes than in the controls. The behaviour of fishes exposed to LC26 (96h) concentrations of-pesticides is discussed. Estuarine fishes appear to be more sensitive and susceptible to pesticides than fresh water fishes. The pesticides affect the locomotory and swimming behaviour of fishes. Loss in weight of fishes exposed to LC60 (96 h) concentration of pesticides was also estimated. The present reportgives a comprehensive account of the toxic nature of these pesticides to fishes.